Hydrophilic trans‐Cyclooctenylated Noncanonical Amino Acids for Fast Intracellular Protein Labeling. (7th July 2016) - Kozma, Eszter; Nikić, Ivana; Varga, Balázs R.; Aramburu, Iker Valle; Kang, Jun Hee; Fackler, Oliver T.; Lemke, Edward A.; Kele, Péter
Abstract: Introduction of bioorthogonal functionalities (e.g., trans ‐cyclooctene‐TCO) into a protein of interest by site‐specific genetic encoding of non‐canonical amino acids (ncAAs) creates uniquely targetable platforms for fluorescent labeling schemes in combination with tetrazine‐functionalized dyes. However, fluorescent labeling of an intracellular protein is usually compromised by high background, arising from the hydrophobicity of ncAAs; this is typically compensated for by hours‐long washout to remove excess ncAAs from the cellular interior. To overcome these problems, we designed, synthesized, and tested new, hydrophilic TCO‐ncAAs. One derivative, DOTCO‐lysine was genetically incorporated into proteins with good yield. The increased hydrophilicity shortened the excess ncAA washout time from hours to minutes, thus permitting rapid labeling and subsequent fluorescence microscopy. Abstract : Fluorescent labeling of intracellular proteins through genetic encoding bioorthogonal chemistry is usually compromised by high background, caused by the hydrophobicity of ncAAs. We synthesized and tested new, hydrophilic TCO‐ncAAs. DOTCO‐lysine could be genetically encoded into proteins, and the increased hydrophilicity permitted rapid labeling for fluorescence microscopy.